EFFECTIVENESS TEST OF PLAY-BASED FOOTBALL WARM-UP MODEL - Qorry Armen Gemael (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2018)
Effectiveness test of play-based football warm-up model involves students of University of Singaperbangsa Karawang who take football courses as research subjects consisting of 150 students. This study was using a quantitative approach. The test was carried out after treatment using True Experimental Design in the form of Pre-test-Post-test Control Group Design. Instrument used in this research and development was a warm-up instrument that was used to collect subject data. The validity test of the instrument sit and reach is 0.979, Static Flexibility Test - Ankle is 0.913, Standing Balance Test is 0.942 while the result of sit and reach reliability test, Static Flexibility Test - Ankle, and Standing balance are 0.940. From the result of validity and reliability test, the warm-up instrument is feasible. Effectiveness test of the model using warm-up tests is needed to determine the readiness of the muscles, joints and body balance, so as to avoid injury after treatment of the model developed. Based on data analysis obtained t-table value is 1.993 with a significance level of 0.05. Because of t-count value 27,765> t-table value 1,993 then H0 is rejected. Based on this information it can be said that the play-based warm-up model in football is effective and can prepare muscles, joint flexibility and body balance so that core activities can be carried out optimally and avoid risk of injury. Keywords: Effectiveness Test, warm-up models, football, play